JETPACK COMPOSE AND XML LAYOUT RENDERING PERFORMANCE COMPARISON - Fjodorovs, Iļja; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The aim of the work is to find out the rendering performance of new Google Android user interface framework “Jetpack Compose”. Author has built two applications for Android platform with identical user interfaces: one uses classic approach with Kotlin + XML layout file, another application is developed using Jetpack Compose. In the results, the performance comparison of each approach is provided.